PERAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN MELALUI MANAJEMEN BERBASIS SEKOLAH DI SD NEGERI KUBANGPARI 02 KECAMATAN KERSANA KABUPATEN BREBES - Jalaludin; Ngurah Ayu Nyoman M; I Made Sudana (STKIP Subang, 2023)
Improving the quality of education is an urgent problem and is deemed necessary to receive serious attention and treatment from various related parties. This is closely related to school leadership and management. Apart from that, in improving the quality of education you must pay attention to all aspects of a school, including input, process and output. The quality of education is deemed necessary to make improvements and changes in various sectors, including leadership and management. The success of a school will only be able to be carried out by effective management, effective management can only be carried out by professional leadership. The things that leaders as managers need to do are: planning and evaluating, organizing, directing and supervising, and monitoring continuous evaluation for further action. This research describes the role of school principals in improving the quality of education through School Based Management implemented at SD Negeri Kubangpari 02, Kersana District, Brebes Regency with the formulation of the research problem: What is the role of leadership in improving the quality of education, How is the management of school principals in improving the quality of education through Based Management Schools, What are the supporting factors and obstacles in improving the quality of education through School Based Management. This research uses a qualitative research approach with a naturalistic phenomenologic type. Research data was obtained using involved observation techniques, in-depth interviews and documentation. Key informants in this research, the principal and teacher.